Android-Based Natural Science Learning Application: Review (UPEJ Unnes Physics Education Journal, 2020)
The use of learning applications is currently increasing from year to year. Learning applications are considered useful in the era of the industrial revolution 4.0, which integrates digital technology. Learning applications that are currently widely used are learning applications using Android-based smartphones. It needs to be seen to what extent the Android-based science learning application has been implemented. Systematic literature review analysis is used to determine the similarities and differences in the journals under review, such as the research objectives, the methodology chosen, and the study's findings. According to keywords, articles are selected through sources from several journals such as ERIC, Elsevier, IJSE, Science Direct, and Google Scholar. The keywords used in the search are android-based learning applications. Search is limited to the period 2016 to 2020. A total of 30 articles have been analyzed based on the systematic literature review steps, including compiling questions, searching, reading titles, abstracts and content, and filtering information from selected articles. Based on the review conducted, it can be concluded that the Android-based science learning application is necessary and essential to be applied and developed. Learning applications have many benefits, including increasing interest in learning, motivation, learning outcomes, learning independence, and understanding concepts.